Keselarasan Karir Siswa dengan Harapan Orang Tua : Adolescent-Parent Career Congruences dan STEM Career Interest - Bagaskara, Bagus; Sulistiobudi, Rezki Ashriyana (Universitas Pendidikan Mandalika, 2023)
This research aims to analyze the role of adolescent-parent career congruence as a variable influencing parental influence on high school students' STEM career interests. This study was non-experimental quantitative research conducted on 68 students from a public high school in Jakarta, majoring in science (MIPA). The research utilized the Adolescent-Parent Career Congruence Scale and STEM Career Interest Scale, employing the convenience sampling method. Data processing was conducted through regression analysis. The results of this study indicated that adolescent-parent career congruence significantly and positively influenced STEM career interest. The dimension with the most significant role was Complementary Support. This finding suggests that parents must actively support their children in discovering their career interests.